Immune Regulation and Antitumor Effect of TIM-1. (20th June 2016) - Du, Peng; Xiong, Ruihua; Li, Xiaodong; Jiang, Jingting
Abstract : T cells play an important role in antitumor immunity, and the T cell immunoglobulin domain and the mucin domain protein-1 (TIM-1) on its surface, as a costimulatory molecule, has a strong regulatory effect on T cells. TIM-1 can regulate and enhance type 1 immune response of tumor association. Therefore, TIM-1 costimulatory pathways may be a promising therapeutic target in future tumor immunotherapy. This review describes the immune regulation and antitumor effect of TIM-1.